Effect of genetic group (Cyprus and Local Male Goats and Their Crosses( on Proximate analysis in LD,SM, and IS muscles: Hassan M. Hassan Yaseen* Amera M. Saleh Al- Rubeii** Saad Mohamed Nada*** - Yaseen, Hassan M. Hassan; M. Saleh Al- Rubeii, Amera; Mohamed Nada, Saad (Journal of Kerbala for Agricultural Sciences, 2016)
This study was conducted at the Ministry of Agriculture research station ruminants which are located in Akerkov / Abu Ghraib, 23 km west of Baghdad, during the period 01.20.2014 until 03.25.2014. And also conducted some tests in the laboratories of Biotechnology Research Center pertaining to the University of AL-Nahrain. The aim of the study is to have a comparison about the characteristics quality of goat meat, which date back to different genetic groups, namely, (Local, Cypriot and bred crosses). The study showed that there were significant differences ( P < 0.05 ) between the different genetic groups regarding proximate analysis when conducting genetic comparisons between local groups and the Cypriot and bred crosses in muscles taken from different parts of the carcasses and all muscles represents a sample taken from that part of it which is the LD (Longissimus dorsi),SM(semimambanosus) and IS(infraspintus). Where it superior the second genetic group (Cypriot) ( P < 0.01 ) , on the other genetic groups in protein percentage in muscles studied while, superior ( P < 0.01 ) fourth genetic Group (Local with CY) in fat percentage in LD ,IS muscles and was superiority ( P < 0.01 ) SM muscle in the third genetic Group (first generation output from the local crosses with Cypriot).As regards to the moisture content there was no differences mention of genetic groups regarding the studied muscle , There was a significant difference ( P < 0.05 ) in LD muscle where superior in all three groups on the third genetic Group and the superiority ( P < 0.01 ) the fourth genetic group in LD muscle of ash percentage while outperforming the third group of SM and IS muscles. ــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــ This paper is part of PhD dissertation of first author تأثير المجاميع الوراثية لذكور الماعز (القبرصي والمحلي وتضريباتهما ) على التحليل الكيميائي للعضلات (LD , SM و IS ) المستخلص أجريت هذه الدراسة في محطة ابحاث المجترات التابعة لوزارة الزراعة والتي تقع في عقرقوف / ابي غريب 23 كم غرب بغداد , خلال الفترة 20/1/2014 ولغاية 25/3/2014 . وكذلك اجريت بعض التحاليل في مختبرات قسم التقانات الاحيائية التابعة لجامعة النهرين , والهدف من هذه الدراسة هو اجراء مقارنة حول جودة خصائص لحم الماعزللمجاميع الوراثية المختلفة ،وهي (ذكور الماعز المحلية، القبرصية وتضريباتهما). وأظهرت الدراسة أن هناك فروق ذات دلالة إحصائية (P <0.05) بين مجموعات وراثية مختلفة بشأن التحليل الكيميائي للعضلات المدروسة عند إجراء المقارنات بين الجماعات المحلية والقبرصية وتضريباتهما في عضلات مأخوذة من مناطق مختلفة من الذبيحة وجميع العضلات يمثل عينة أخذت من ذلك الجزء والتي هي عضلات LD (Longissimus dorsi) SM(semimambanosus) IS(infraspintus) .فقد تفوقت معنويا المجموعة الوراثية الثانية والتي تمثل الماعز القبرصي(P <0.01) على باقي المجاميع الوراثية في صفة نسبة البروتين في العضلات المدروسة , في حين تفوقت معنويا (P <0.01) المجموعة الوراثية الرابعة والتي تمثل الماعز المحلي مع القبرصي على باقي المجاميع في صفة نسبة الدهن في العضلات LD , IS في حين تفوقت معنويا (P <0.01) المجموعة الوراثية الثالثة ( الجيل الاول ) على باقي المجاميع الوراثية في عضلة SM , اما مايخص صفة المحتوى الرطوبي لم يكن هناك اي فروقات معنوية تذكر بين المجاميع الوراثية في العضلات SM و IS المدروسة . في حين كان هناك فروقات معنوية (P <0.05) في صفة نسبة الرطوبة في عضلة LD حيث تفوقت المجاميع الوراثية الاولى والثانية وارابعة جميعها على المجموعة الثالثة , اما صفة نسبة الرماد فقد اوضحت الدراسة وجود فروقات معنوية ((P <0.01 حيث تفوقت المجموعة الوراثية الرابعة على باقي المجاميع الوراثية في العضلة LD , في حين تفوقت المجموعة الورا ثية الثانية على باقي المجاميع الوراثية في العضلات SM و IS .